AKTIVITAS ANTIPLASMODIUM In vitro DAN IDENTIFIKASI GOLONGAN SENYAWA DARI EKSTRAK ETANOL BATANG MANURAN (Coptosapelta tomentosa Valeton ex K.Heyne) ASAL KALIMANTAN SELATAN - Arnida; Eka Rahmawaty Sahi; Sutomo (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2017)
The resistance of Plasmodium to antimalarial drugs resulted in treatment failure. It posed a threat in the absence of alternative effective drug for the resistance. Therefore, the availability of new antimalarial drug was highly required to overcome this problem. Exploration of new antimalarial drugs was conducted using various methods, including exploration and development of natural substance. The selection of the natural substance was usually conducted on the basis of empirical use by people. Manuran (Coptosapelta tomentosa Valeton ex K.Heyne) was used by people living in Kotabaru of South Kalimantan to treat malaria. An in vitro antiplasmodial activity test was carried out to the resulting ethanol extracts of the plant using candle jar method. The resulting data was processed using probit analysis to give the IC50 value. Based on the identification of chemical content with phytochemical screening and Thin Layer Chromatography shows the presence of flavonoids, terpenoids, saponins, tannins and anthraquinones in C. tomentosa Valeton ex K.Heyne) stem. The in vitro antiplasmodial activity of the ethanol ekstract of C. tomentosa Valeton ex K.Heyne) were classified to be active, the IC50 values 45,864 ± 0,76 µg/mL.